2007
DOI: 10.1161/strokeaha.107.486738
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Indices of Apoptosis Activation in Elastase-Induced Aneurysms After Embolization With Platinum Coils

Abstract: Background and Purpose-Even though endovascular coils have been widely used for the treatment of intracranial aneurysms, the cellular and molecular responses of aneurysms to the coils after embolization remain poorly understood. The aim of the present study was to understand the mechanism of apoptosis in aneurysms embolized with platinum coils in the rabbit model of elastase-induced aneurysms. Methods-Elastase-induced saccular aneurysms were created at the origin of the right common carotid artery in 30 rabbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…16 Moreover, both TNF-␣-mediated extrinsic and Bcl-2-mediated intrinsic apoptotic pathways induced apoptosis in a rabbit aneurysm model. 28 These data, therefore, indicate that genes involved in both intrinsic and extrinsic apoptotic pathways may contribute to the pathogenesis of IAs.…”
Section: Discussionmentioning
confidence: 86%
“…16 Moreover, both TNF-␣-mediated extrinsic and Bcl-2-mediated intrinsic apoptotic pathways induced apoptosis in a rabbit aneurysm model. 28 These data, therefore, indicate that genes involved in both intrinsic and extrinsic apoptotic pathways may contribute to the pathogenesis of IAs.…”
Section: Discussionmentioning
confidence: 86%
“…Caspase-9 is a crucial up-stream initiator enzyme in the mitochondria-mediated apoptotic pathway and its activation can be achieved either by cleavage or by association with apoptotic protease activating factor 1 (Apaf-1) to form the active apoptosome [36]. In the death receptor pathway, ligation of a receptor belonging to the tumor necrosis factor (TNF) receptor family leads to the induction of apoptosis through activation of caspase-8 [37]. Both activated caspase-9 and activated caspase-8 can further catalyze down-stream caspases including the major effector enzyme caspase-3, which leads to DNA fragmentation and subsequently to apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Histologic studies of rabbit aneurysms have demonstrated that there is increased expression of activated cleaved caspases at four weeks following coil embolization 27 . Apoptosis of myofibroblasts in the aneurysm dome has been shown to be mediated by both intrinsic (Bcl-2/mitochondrial mediated) and extrinsic (TNF-alpha/receptor mediated) pathways of apoptosis 30 .…”
Section: Histologic Findings In Animal Models Following Bare Platinummentioning
confidence: 99%